The evolution of Cicada songs contrasted with the relationships inferred from mitochondrial DNA (Insecta, hemiptera) - Fonseca, P. J. (2014)
The molecular phylogeny of nine Palaearctic species of cicadas (Hemiptera, Cicadoidea) was inferred using two mitochondrial DNA genes, Cytochrome Oxidase I and II. The two main groups detected, namely species within Tettigetta and Tympanistalna, as well as the two species investigated in the genus Cicada, are robustly supported across the analytical methods. The structure of the song syllables, generated during single tymbal cycles of males of the analysed group of species is remarkably consistent in these two phyletic lines. This reflects the morphology and the mechanics of the tymbal. However the higher level song patterns, which depend on the activity of the central nervous system and have evolved to advertise receptive mates, do not seem to be consistent with either the inferred molecular topology or the basic tymbal cycle. The observed similarities between the molecular phylogeny and the basic tymbal cycles seem to reflect the basic conservative nature of the tymbal structure, while the discrepancy between the former and the calling song pattern is probably related to the high plasticity of the pattern generator in the central nervous system and dependent on species-specific selection.